Line constant measurements and loading current test in long-distance 275 kV GIL. - Miyazaki, A. (IEEE Transactions on power delivery)
This paper reports on the results of a loading current test and measurements of the line constants of a long-distance gas-insulated transmission line (GIL) in a tunnel. The loading current test was carried out at 80% rated current, to verify the soundness of the thermal expansion and contraction of the GIL. As a result, the performance of the GIL was confirmed to be appropriate in terms of the thermal expansion and contraction. With respect to the line constants and transient enclosure voltage, each of the measured values was found to be at an appropriate level presenting no problem for the service operation of this line